Evaluasi Pelaksanaan Program Kampus Mengajar pada Mahasiswa Fakultas Teknik Universitas Negeri Padang - Al Hadad, Habel Wilefri; Haq, Syaiful; Mardizal, Jonni; Zuwida, Nidal (Lembaga Yasin AlSys, 2025)
The Teaching Campus Program provides direct experience for students to collaborate with teachers and principals in improving the quality of learning, especially in literacy, numeracy, and technology adaptation. This study aims to analyze the implementation of the teaching campus program for engineering students at Universitas Negeri Padang. This research uses a descriptive method with a mixed method approach, which combines quantitative and qualitative approaches to obtain more comprehensive data. The purpose of this study is to describe the suitability of the placement of Teaching Campus Program students with their original study program at the Faculty of Engineering, Universitas Negeri Padang. The research population of 35 students who were all sampled through the total sampling technique. The research variable is the evaluation of the implementation of the Teaching Campus Program based on the CIPP (Context, Input, Process, Product) evaluation model. Based on the research findings, it can be concluded that the evaluation of the implementation of the teaching campus program for FT UNP Students as a whole is in the “Good” criteria. This shows that the Teaching Campus activities have been carried out well from the various aspects evaluated. However, there are still several indicators within each dimension that need improvement in order for this program to achieve the “Excellent” category and for the policies to be implemented optimally.